Engführungen. Celans etho-poetisches Schreiben „nach“ (und als Teil) der Natur. Ein Essay - Camilla Miglio (Universität Trier, 2021)
This article investigates the relation between nature, ethics, and poetics in the work of Paul Celan, using „Engführung“ [“Stretto”] as a starting point. The readings from Celan’s library testify to his careful rethinking of what “reality” means. Applying the terminology and research of geology, physics, and, in particular, quantum mechanics, opens up an interpretative horizon for Celan’s poetry that can be configured according to the laws of entanglement as well as the form of a multidimensional ‚Raumgitter‘. The human and ethical elements of intentionality and being-in-the-world are not obliterated but rather subordinated to the natural itself. Celan goes beyond the idea of a subject-observer of the world-as-object and offers us a perspective in which language, as well as humanity and intentionality (poetic and otherwise), is merely one cosmic manifestation – part of nature itself. Language, like nature, shows different and changing states of being. It can be metamorphic but also sedimentary; conglomerate but also fluid like the elements present in nature. It is not a metaphorical analogy but a changing material state. It is non-local, dynamic, and provisional, like the relationality of quantum aggregations. Writing ‚nach der Natur‘ is, for Celan, who makes the knowledge and vocabulary of the natural sciences his own, to recover this metamorphic, provisional dimension of language – inside and outside time, probabilistic, invisible at a macroscopic level. By writing in and as nature in this way, poetry resists the destruction of what “happened” [geschehen] at the camps in the most devastating way.